Ultrasmall Solid-Lipid Nanoparticles via the Polysorbate Sorbitan Phase-Inversion Temperature Technique: A Promising Vehicle for Antioxidant Delivery into the Skin - Francesca Della Sala; Assunta Borzacchiello; Chiara Dianzani; Elisabetta Muntoni; Monica Argenziano; Maria Teresa Capucchio; Maria Carmen Valsania; Annalisa Bozza; Sara Garelli; Maria Di Muro; Franco Scorziello; Luigi Battaglia (MDPI AG, 2023)
Solid lipid nanoparticles promote skin hydration via stratum corneum occlusion, which prevents water loss by evaporation, and via the reinforcement of the skin's lipid-film barrier, which occurs through the adhesion of the nanoparticles to the stratum corneum. The efficacy of both phenomena correlates with lower nanoparticle size and the increased skin permeation of loaded compounds. The so-called Polysorbate Sorbitan Phase-Inversion Temperature method has, therefore, been optimized in this experimental work, in order to engineer ultrasmall solid-lipid nanoparticles that were then loaded with α-tocopherol, as the anti-age ingredient for cosmetic application. Ultrasmall solid-lipid nanoparticles have been proven to be able to favor the skin absorption of loaded compounds via the aforementioned mechanisms.